2012
DOI: 10.1371/journal.pone.0045706
|View full text |Cite
|
Sign up to set email alerts
|

IL-27-Induced Gene Expression Is Downregulated in HIV-Infected Subjects

Abstract: ObjectiveTo characterize the effect of HIV infection on IL-27-induced gene expression.DesignDuring HIV infection, cytokine expression and function become deregulated. IL-27 is an important modulator of inflammatory responses. Interestingly, IL-27 can inhibit HIV replication in T cells and monocytes, implicating IL-27 as a potential adjunct to anti-viral treatment. Our previous work demonstrated that circulating HIV may suppress IL-27 expression, therefore, this study, in continuation of our previous work, aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…FCM was used with PBMC as positive control (35). The results demonstrated that both gp130 and IL-27Ra were expressed in hPMSCs (Fig.…”
Section: Phenotypic Characteristics and Differentiation Of Hpmscsmentioning
confidence: 91%
“…FCM was used with PBMC as positive control (35). The results demonstrated that both gp130 and IL-27Ra were expressed in hPMSCs (Fig.…”
Section: Phenotypic Characteristics and Differentiation Of Hpmscsmentioning
confidence: 91%
“…Some studies have also looked at whether cells obtained directly from HIV-1 infected donors have an impaired response to IL-27. Exogenous IL-27 was administered to monocytes from HIV-1 infected donors and their responsiveness was compared to monocytes from uninfected controls [41]. In monocytes obtained from HIV-1 infected donors, IL-27 treatment led to lower levels of expression of the IL-27 receptor subunit, gp130, compared to healthy controls.…”
Section: The Role Of Il-27 In Hiv-1 Infectionmentioning
confidence: 99%
“…Subsequent studies have established that IL-27 and IL-27 signaling exert a suppressive effect on CD4 + T cells and limit immune-mediated pathology associated with various pathological conditions192021. HIV-infected individuals when compared to uninfected controls demonstrate low plasma IL-27 levels22, down-regulated expression of IL-27R and suppressed production of cytokines in response to IL-2723. The effect of IL-27 on the immune response to CMV infection is unknown.…”
mentioning
confidence: 99%